Implementasi Game-Based Learning Berbasis Kartu Domino untuk Meningkatkan Pemahaman Materi pada Siswa Sekolah Menengah Pertama - Muhammad Nasrul Rojab; Milda Maulida; Indah Darmayani; Tetep; Anita Murdayanti (PTK: Jurnal Tindakan Kelas, 2025)
Pancasila and Citizenship Education (PPKn) learning is often considered abstract and less interesting by students, especially in understanding the concept of diversity within the framework of Bhinneka Tunggal Ika. Learning innovation is needed so that the material can be understood contextually and enjoyably. This study aims to implement a Game-Based Learning model based on domino cards to improve the understanding of grade IX students of SMP Negeri 5 Tarogong Kidul on the material of diversity within the framework of Bhinneka Tunggal Ika. This study uses the Classroom Action Research (CAR) method of the Dave Ebbutt model which is cyclical. The study was conducted in two cycles, each including the planning, action, observation, and reflection stages. The research instruments included observation, questionnaires, interviews, and comprehension tests. Data were analyzed qualitatively and quantitatively. The results showed that the use of domino cards as a game-based learning medium can increase students' active involvement, critical thinking, and understanding of the values of diversity. The average understanding score increased from 78.9 in cycle I to 86.7 in cycle II. This means that implementing game-based learning using domino cards has proven effective in improving student understanding. This model aligns with the characteristics of active and kinesthetic students and supports meaningful and contextual PPKn learning.